Adubação fosfatada em variedades de cana-de-açúcar cultivadas em ambiente restritivo de cerrado - Ferreira, Marina Munhoz Rosato [UNESP] (2015)
The phosphorus is the nutrient that most limits the production of sugarcane grown in the cerrado region of soil in production environments called restrictive and the varietal cast is limited to these regions. The importance of management and phosphate fertilizer for the cultivation of sugarcane is in terms of productivity, technological quality and longevity of the plantation. With the objective to evaluate the performance of early varieties of sugarcane to four doses of phosphorus fertilizers, applied in the planting furrow, in cerrado soil and in environments of production D, was conducted this experiment, crop 2014/15, at Sao Jose Farm, area administered by Usina Alcoolvale S/A, located in Aparecida do Taboado, state Mato Grosso do Sul, Brazil, in a Red Latosol. The experiment was a randomized blocks design was used in a factorial scheme 4x4 with 16 treatments consisting by four sugarcane varieties (CTC 1, CTC 9001, RB835054 and RB965902) and four doses of phosphorus fertilizers (0, 150, 300 e 450 kg ha -1 of P 2 O 5 ) applied in the planting furrow, in four replications. Using the source of triple superphosphate. The experimental plots were constituted of five rows sugarcane with spacing of 1.5 m in-between rows by 10 m long. The variables evaluated were: tillering to 27, 61, 119, 181 and 265 DAP (days after planting) and leaf area index to 207 and 362 DAP, nutrients leaves concentrations, biometrics characteristics, stalk yield and agroindustrial production and technological analyses. The variety RB965902 had the lowest values of the characteristics that make the quality of the raw material. The doses of phosphorus fertilizers applied in the planting furrow provided linear increase in leaf area index, in foliar contents of N, P and Mg, but not affect the agronomic characteristics, stalk yield and agroindustrial production and technological quality of the sugarcane. Occurs influences the ...